Development and Validation of an Oral Health Literacy Measurement for Primary School Children in Thailand - Pinpinut Wanichsaithong; Piyada Prasertsom (Hindawi Limited, 2022)
Background. Oral health promotion programs have been implemented in primary schools for many years in Thailand. Oral health literacy has been introduced as a health promotion outcome; however, no assessment tool has been developed for this age group. The objective of this study was to develop and validate the Test of Functional Health Literacy in Dentistry for Primary School Children (P-TOFHLiD). Materials and Methods. The P-TOFHLiD was developed by modifying contents and outlines using a previously validated tool for older adults, then verified by two experts for face validity. A cross-sectional study was conducted with samples collected from 118 grade-six students from two government schools in Chiang Mai Province, Thailand. The P-TOFHLiD and a previously validated word recognition test were administered, followed by oral examination to assess reliability, concurrent validity, convergent validity, and predictive validity and establish the cut-off score of the tool. The statistical analysis was performed using SPSS version 25. Results. The internal reliability of P-TOFHLiD was good (α = 0.808). The correlation coefficient between the P-TOFHLiD and grade point average was 0.478 (p value <0.001), which is the represented concurrent validity of the tool. Coefficients between P-TOFHLiD and a word recognition test was 0.422 (p-value <0.001) for convergent validity. P-TOFHLiD was significantly correlated with the number of missing teeth from tooth decay (p-value <0.05), but the correlation coefficient was poor (r = −0.100). The cut-off scores for adequate oral health literacy were set at ≥21 out of the total scores of 26. Conclusion. P-TOFHLiD presented good validity and reliability and was ready to use for oral health promotion program evaluation. However, the predictive validity of the P-TOFHLiD in predicting oral health status was questionable only.